Potential of Hydroxysafflor yellow A, the main compound of Kasumba Turate (Carthamus tinctorius ) as Anti-Inflammatory in Lung, Liver and Cardiac Tissues: A Literature Review - Hansur, Lismayana; Aras, Dara Ugi; Endah Dwijayanti (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Inflammation is the body's physiological response to stimuli such as infection, trauma and chronic disease. Its exacerbation can lead to deterioration in health and damage to tissues in organs such as the lungs, kidneys and liver. The drive behind the development of anti-inflammatory drugs is to improve treatment efficacy and reduce adverse effects. The primary aim of this article is to deliberate on the pharmacological properties of compound from C.tinctorius as an anti-inflammatory agent. Through an extensive study of data we made a literature review of 17 research conducted to unravel the potential of compound from C.tinctorius as an anti-inflammatory agent. The ability of Carthamus tinctorius to alleviate inflammation is demonstrated by its ability to inhibit the activation of the NF-κB pathway and suppress the binding of the TGF-β1 promoter. These molecular processes hold the promise of ameliorating lung injury by attenuating the inflammatory response through suppression of the TLR 4-dependent signalling pathway, thereby improving the health of rats suffering from pulmonary fibrosis, a condition characterised by inflammation and vascular tissue repair. In addition, compounds in C. tinctorius are effective in reducing T lymphocyte (CD4) apoptosis in sepsis through their anti-inflammatory and anti-apoptotic effects. The anti-inflammatory mechanism is also demonstrated by reducing inflammatory cytokines such as IL-6 in the lungs, kidneys and liver.